Development of Android-Based Mobile Application Using Gyroscope Sensor (International Journal of Innovative Research in Computer Science & Technology, 2022)
The idea of this project comes into the  picture from various uses of sensors that are present in our  surroundings. So, we can actually play with them by using  two or more sensor mechanisms that end up as new  inventions. Therefore, we are keen to look forward to one  of the highly scoped and well-furnished sensors i.e., Gyroscope Sensor with an element of Light Sensor. This  sensor is capable of measuring the orientation of the body  and the angular velocity of the object. In our android  project, we embedded the flashlight feature in the Gyro  sensor’s angle alteration logic. This mechanism  successfully leads to the flashlight of the camera getting  ON & OFF when the device is tilted or shifted along the  reference angle. This collaboration of sensors plays an  important role for a device that does not have that feature
Keywords: Gyroscope Sensor; Android; Mobile Application; Android Based Mobile Application; Types of Sensors